Analysis of the Carrying Capacity of Road Infrastructure Towards the Acceleration of Economic Development Performance of Fakfak Regency (Case Study of Community Readiness for the Development of Siboru Airport Road Access) - Joana Andalina Risamasu; Pompong B. Setiadi; Sri Rahayu; Rifda Fitrianti (RTTM, 2024)
The existence of Siboru airport replacing Torea airport in Fakfak district is expected to expand and accelerate regional economic development. The carrying capacity of available road infrastructure is important to increase its use as an economic resource, especially for the surrounding community. The research aims to find out various things that need to be done by the government together with the community and business actors to improve aspects of the usefulness of the carrying capacity of access road infrastructure between Fakfak city and Siboru airport based on current conditions. Descriptive research uses an empirical survey approach through in-depth interview techniques. The survey results were analyzed using qualitative analysis tools combined with quantitative analysis tools in stages. The research results concluded that the government together with the community and business actors need to build synergy to build business efforts in order to increase the utilization of the carrying capacity of road infrastructure connecting the city of Fakfak with Siboru airport. Building a rest area accompanied by managing several stopping points that have panoramic views for Instagrammable photo spots can be a short-term option that needs to be worked on immediately.